Alterações no desenvolvimento de Lactuca sativa L. e Dalbergia miscolobium Benth. produzidas por extratos de folhas de Brachiaria decumbens Stapf. e Melinis minutiflora Beauv - Bonfim, Daniela Cristina (Universidade Federal de São Carlos, 2007)
The present study objected to appraise in vitro the kind of interference that is produced by addicion of leaves extracts Brachiaria decumbens Stapf and Melinis minutiflora Beauv. (exotic species, alien weeds) collected in raining season (12/01/2006) and dry season (10/08/2006) over germination and initial development of Lactuca sativa L. (bioindicator species) and Dalbergia miscolobium Benth. (native species of savanna). It were verified also that pH and osmotic potencial of both B. decumbens and M. minutiflora extracts did not cause interference in seed germination indices. The germination of D. miscolobium was not affected by leaves extracts obtained of material collected in dry season and raining season. The germination speed was more sensitive to action of extracts than germination percentage of L. sativa. The total length of the seedlings was reduced in practically all treatments when, compared with the control group, however significative statistical differences were observed just in above-ground part of the seedlings of L. sativa treated with leaves extracts of B. decumbens collected in dry season. The L. sativa root was stimulated when leaves extracts of M. minutiflora collected in dry season was added in Petri dishes. For seedlings of D. miscolobium the leaves extracts of B. decumbens collected in dry season decreased the length of the above-ground part and the root, and the same was observed for leaves extracts of M. minutiflora collected in the raining season. Anatomy studies of root-tip cells carried of D. miscolobium e L. sativa showed that the extracts of B. decumbens e M. minutiflora cause damage on the root cells of seedlings with different intensities, but the root cells of D. miscolobium, showed alterations most emphasized.
Keywords: Alelopatia; Gramíneas invasoras; Dalbergia miscolobium; Cerrado; Allelopathic effects; Growing; Germination percentage; CIENCIAS BIOLOGICAS::ECOLOGIA